Natural Compounds: A Potential Treatment for Alcoholic Liver Disease? - Yan, Junbin; Nie, Yunmeng; Luo, Minmin; Chen, Zhiyun; He, Beihui (Frontiers in Pharmacology, 2021)
Excessive alcohol intake is a direct cause of alcoholic liver disease (ALD). ALD usually manifests as fatty liver in the initial stage and then develops into alcoholic hepatitis (ASH), fibrosis and cirrhosis. Severe alcoholism induces extensive hepatocyte death, liver failure, and even hepatocellular carcinoma (HCC). Currently, there are few effective clinical means to treat ALD, except for abstinence. Natural compounds are a class of compounds extracted from herbs with an explicit chemical structure. Several natural compounds, such as silymarin, quercetin, hesperidin, and berberine, have been shown to have curative effects on ALD without side effects. In this review, we pay particular attention to natural compounds and developing clinical drugs based on natural compounds for ALD, with the aim of providing a potential treatment for ALD.